DEVELOPMENT OF INITIATIVE QUARTIFICATES IN PRIMARY STUDENTS - Ismailova Lobar (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This article analyzes the theoretical foundations and methodological approaches to developing initiative qualities in primary school students. The structural components of initiative are identified and effective pedagogical technologies that serve to form it are highlighted. Also, the didactic conditions for developing initiative based on a competency-based approach are substantiated.